Possible Role of Local Anesthetics in Permanent Lower Limb Motor Paralysis After Epidural Anesthesia: A Case Report - Kamiya, Ichiro; Kim, Chol; Kageyama, Atsuko; Ishikawa, Masashi (Journal of Nippon Medical School, 2025)
We present a case of permanent bilateral lower limb paralysis after epidural anesthesia. A 71-year-old woman (height 159 cm; weight 48.5 kg; American Society of Anesthesiologists Physical Status 2) with a history of hypertension (treated with nifedipine), benign goiter (under surveillance), surgeries for appendicitis, and a previous left humerus fracture had received general anesthesia with epidural anesthesia during two surgical procedures, namely, laparoscopic-assisted low anterior resection with colostomy and laparoscopic-assisted colostomy closure. She developed left-predominant lower limb paralysis after the first epidural anesthesia (using ropivacaine and levobupivacaine). The symptoms had no identifiable cause, persisted after removal of the epidural catheter, and gradually resolved during rehabilitation. Her lower limb paralysis recurred and progressed, however, after the second epidural anesthesia (using levobupivacaine alone), and she has abnormal spinal reflexes and elevated myelin basic protein in cerebrospinal fluid. Although these findings suggested that bilateral lower limb paralysis was caused by a lesion in the central nervous system (thoracolumbar spinal cord), postoperative MRI scans of the vertebrae/spinal cord and head failed to identify the site of the damage. We concluded that permanent bilateral lower limb paralysis was likely caused by epidural anesthesia, but the mechanism could not be identified.